A Mixed-mode Vector-based dataflow approach for modeling and simulating LTE physical layer - Chia-Jui Hsu; Pino, José Luis; Fei-Jiang Hu (Design Automation Conference, 2010)
Long Term Evolution (LTE) is one of the emerging technologies toward 4th generation mobile wireless networks. For LTE physical layer development, electronic system level (ESL) tools are widely used to assist design and verification processes. Among various modeling technologies underlying ESL tools, synchronous dataflow (SDF) and its related models of computation have been successfully used to model and simulate many wireless standards. However, LTE physical layer involves dynamically varying data processing rates that make SDF insufficient due to its constant-rate constraint. In this paper, we present a novel approach, called Mixed-mode Vector-based Dataflow (MVDF), to efficiently model and simulate LTE physical layer by exploring the matched-rate nature of LTE and by combining static and dynamic dataflow technologies. We have implemented MVDF in an ESL tool, called SystemVue, along with a complete LTE physical layer library. With the implementation, we are able to create LTE reference designs for performance measurements. Our simulation results successfully match the standard requirements and justify the capability of MVDF.